Comparative Study on Histochemical Expression of CD34 in Different Variants of Ameloblastoma: CD34 Expression in Ameloblastoma Variants - Bashir, Nasiha; Obaid, Maria; Iqbal, Fatima; Maryam, Hoor; Naushin, Tehmina; Khan, Abbas Saleem (Pakistan Journal of Health Sciences, 2025)
Ameloblastoma is a benign, locally aggressive, tumor of the oral cavity having a high propensity for recurrence. The growth potential of the tumor is linked to the proliferation of preexisting vasculature and is reflected in CD34 expression. has been rephrased as “Mean Vascular Density (MVD) which measures CD34 expression, aids in predicting this proliferation. Objectives: To evaluate the biological behavior of different variants of Ameloblastoma according to expression of CD34 and to correlate it with age and gender. Methods: The present study was analytical, cross-sectional study composed of total 40, already diagnosed cases of ameloblastoma. Immuno-histochemical expression of CD34 was analyzed. Results: Follicular variant has more growth potential in females 21 (62%) and males reveal more vascular growth in plexiform 19 (80%) acanthomatous (50%) and unicystic variant (50%). More endothelial proliferation in age group of > 40 years was seen in follicular variant, whereas, in age group of < 40 years, plexiform type was more dominant. However, relationship between the age groups and MVD scores were found to be insignificant (p > 0.05). Relationship between CD34 expression in ameloblastoma and its histological variants were also found to be statistically non-significant (p=0.9). Conclusions: All variants display highest Mean Vascular Density (MVD) score in posterior mandible. Follicular variant has more growth potential in females while in males it is found more in plexiform, acanthomatous and unicystic variants. More epithelial proliferation in the follicular variety is observed in the age group over 40, whereas more plexiform type was shown in the age group below 40.